The Evaluation of Competitive Intelligence Maturity Level in Hotels (Study on Yazd 3 and 4 star Hotels) - Mehdi Ebrahimi; Mehdi Karroubi; Zohreh Mohammadi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2015)
within hotels. This paper aims to estimate the competitive intelligencematurity within Yazd hotels based on its final function. The project isempirically based and is characterized by exploratory approach. Aquestionnaire-oriented survey covering 56 managers of Yazd 3 and 4star hotels as samples was conducted to collect data for the study .Thefindings revealed that CI factors in hotel can be best examined bytechnology intelligence, social and strategic intelligence, marketingand commerce intelligence and competitors intelligence. The findingsindicate that Yazd hotels CI maturity is above the average and in agood condition. Also all of the CI factors maturity was estimatedabove the average. The study provides empirical evidence that CIactivities in 4 star hotels rather than 3 star hotels got better scores.Finally it was shown that in these hotels the focus of the managementis more on inside CI activities than outside one. There are somelimitations; first, the hotels chosen for the study were mainly 3 and 4star hotels; second, this survey was limited to one city of Iran. Thus,the results may not be applicable to all hotels